Measurement of CP observables in B± → DK*± decays using two- and four-body D final states. (November 2017) - Aaij, R.; Adeva, B.; Adinolfi, M.; Ajaltouni, Z.; Akar, S.; Albrecht, J.; Alessio, F.; Alexander, M.; Alfonso Albero, A.; Ali, S.; Alkhazov, G.; Alvarez Cartelle, P.; et al.
Abstract Measurements of CP observables inB ± →DK *± decays are presented, whereD denotes a superposition ofD 0 and D ¯ 0 D^0 meson states. Decays of theD meson toK − π +, K − K +, π − π +, K − π + π − π + andπ − π + π − π + are used and theK *± meson is reconstructed in theK S 0 π ± final state. This analysis uses a data sample ofpp collisions collected with the LHCb experiment, corresponding to integrated luminosities of 1 fb−1, 2 fb−1 and 1.8 fb−1 at centre-of-mass energies s = 7 s=7 TeV, 8 TeV and 13 TeV, respectively. The sensitivity of the results to the CKM angleγ is discussed.